Evaluating User Experience of OpenProject at PT Promanufacture Indonesia Salatiga using the User Experience Questionnaire (UEQ) Method - Adventien, Irene Puspa; Maria (SCOPUS ID: 57093633500), Evi (Sistemasi: Jurnal Sistem Informasi, 2025)
The purpose of this study is to evaluate the user experience of OpenProject at PT Promanufacture Indonesia Salatiga using the User Experience Questionnaire (UEQ) method. The UEQ method was chosen for its effectiveness in measuring user satisfaction and analyzing the quality of user experience across six main evaluation scales: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data were collected from 100 OpenProject users at PT Promanufacture Indonesia Salatiga and analyzed based on the average scores for each scale category. The results showed that most categories received positive ratings, with average scores above 0.8, except for the attractiveness scale, which fell into the "below average" category. The benchmark analysis indicated that the dependability scale ranked as "excellent," while the perspicuity and efficiency scales were categorized as "above average." The stimulation and novelty scales were rated as "good." These findings suggest that OpenProject excels in efficiency, dependability, and novelty, although improvements in visual appeal are necessary to enhance user comfort. This study contributes to the development of user experience theory in digital project management systems and reinforces the validity of the UEQ as a UX evaluation tool in professional software environments. It also highlights that while attractiveness may not be a primary factor in project management systems, it still plays a role in fostering user engagement. Therefore, UX models for enterprise software should strike a balance between functionality and aesthetics. The results of this research provide valuable insights for companies seeking to improve user experience and the effectiveness of project management systems.